Interdisciplinary Approach to Diabetes Management: Integrating Pharmacy, Nursing, Health Informatics, and Laboratory Services for Improved Patient Outcomes - Ahad Azmi Alnoory; Lamyaa Saud Almatani; Khlood Esmaeil Alhawsawi; Ghadeer Tariq Bakhsh; Mohammed helal shafi alluqmani; Ali saud Altalalwah; Nawal Hasan Sahli; Mansour yahya almalki; Bashayer Yahya Zakri; Fahad Ibrahim Al-Zabni; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Diabetes mellitus is a serious public health concern that requires efficient management techniques due to its increasing prevalence. A small percentage of diabetics can reduce and maintain their normal blood glucose levels, and many struggle to follow their doctor’s recommendations for self-management. To help diabetes patients obtain better outcomes, interdisciplinary teams are a potential strategy.One promising approach to improving diabetes outcomes is interdisciplinary care that incorporates pharmacy, nursing, health informatics, and laboratory services. Aim:Investigating the effectiveness of a multidisciplinary approach in the management of diabetes is the goal of this review, which places special attention on the roles that various healthcare professionals perform as well as the integration of informatics and laboratory services. Result and Discussion: Multidisciplinary teams of pharmacists, nurses, and health informatics experts improved clinical outcomes, such as better lipid profiles, blood pressure control, and glycemic control (HbA1c). Health informatics tools enhanced communication and decision-making, while laboratory services offer vital monitoring for optimal care. The combination of many medical specializations leads to more comprehensive and effective diabetic care. This approach improves clinical outcomes while reducing healthcare costs. Future research should concentrate on larger trials to validate these findings and explore ways to optimize interdisciplinary collaboration in diabetes care. Conclusion: It has been shown that the interdisciplinary approach to diabetes care, which integrates pharmacy, nursing, health informatics, and laboratory services, greatly improves patient results, including better glucose control and overall health management. This paradigm promotes patient monitoring and decision-making by promoting team-based care. While encouraging, further research is needed to fully validate the effectiveness of these integrated care models and enhance techniques for their broader use in the management of diabetes, particularly large-scale studies.